A super compact self-powered device based on paper-like supercapacitors. Issue 8 (29th January 2019) - Luo, Zhiling; Liu, Changhong; Fan, Shoushan
Abstract : A novel self-powered device was fabricated by adding one small piece of metal foil onto a supercapacitor. The device can be self-charged to more than 0.7 V when touched by a wet swab. This slender device demonstrates impressive output performance and can drive a vibrating motor. This study provides a novel energy source for self-powered wearable electronics. Abstract : To achieve the direct storage of harvested energy, energy harvesting and storage techniques should be further developed separately, but the integration of these two areas should also be considered. In this work, by attaching a piece of Al foil and qualitative filter paper onto a paper-like supercapacitor (SC), a super compact self-powered supercapacitor (SPSC) was successfully fabricated. The hybrid device can be charged to more than 0.7 V when a wet swab is used, and this easy operation means that it can be charged when touched by a finger. The self-powered property is based on the effective integration of a metal–air cell and SC, allowing the dual-function electrodes to convert chemical energy into electric energy and store it in the SC directly. Our SPSC demonstrates superior output performance when compared to a single metal–air cell and can power a vibrating motor after the self-powered process. A higher output voltage can be achieved by assembling super compact self-powered supercapacitors (SCSCs) in series. This SPSC provides a new reference in the study of energy technology and self-powered wearable electronics.